PENGEMBANGAN ELECTRONIC MODULE ASAM BASA BERBASIS ETNOSAINS DENGAN MODEL CULTURALLY RESPONSIVE TRANSFORMATIVE TEACHING (CRTT) - Zeles, Trisia Monica; Rina Elvia; Wiwit (ALOTROP, 2025)
This study aims to improve students’ conceptual understanding in a contextual and meaningful way through the development of an acid-base e-module based on ethnoscience using the Culturally Responsive Transformative Teaching (CRTT) model. The research employed a Research and Development (R&D) method with the 4D model, limited to the Develop stage. The instruments used included validation sheets, student response questionnaires, and concept understanding tests. Validation results showed that the e-module was highly valid, with a score of 82.72% for content and 87% for media. Student responses were also very positive, with a score of 90.66%. The average N-Gain was 0.83, indicating a high increase in conceptual understanding, particularly in the indicator of relating concepts (0.86). The e-module integrates local ethnoscientific elements from Rejang Lebong culture, such as lemea and candied kedondong, into the acid-base topic. The findings suggest that this e-module is effective for chemistry learning and serves as an innovative, contextual teaching material that supports local cultural preservation. Keywords: E-module, Acid-Base, Ethnoscience, CRTT, Concept Understanding.